Efektivitas Roadmap Pasar Modal Syariah OJK 2020–2024 dalam Meningkatkan Literasi dan Inklusi Keuangan Syariah di Indonesia - Indah Tri Sari Harahap; Keisya Putri Balqis; Wahyudin; Maryam Batubara (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of the Modal Syariah program initiated by Indonesia’s Financial Services Authority (OJK) during the 2020–2024 period in improving Islamic financial literacy and inclusion. The program is part of OJK’s strategic efforts to strengthen the national sharia finance ecosystem through public education, product development, digital infrastructure enhancement, and stakeholder collaboration. The analysis shows a significant increase in Islamic financial literacy, from 8.93% in 2019 to 39.11% in 2024. However, the level of financial inclusion remains relatively low, reaching only 12.88%. This gap reflects that while public understanding of Islamic financial products has improved, actual usage remains limited. Low adoption is attributed to limited access, uneven distribution of Islamic financial institutions, lack of competitive sharia-based products, and uneven digitalization. The study recommends follow-up strategies focusing on improving financial inclusion through digital service innovation, need-based incentives, and integration of Islamic finance with the micro, small, and medium enterprises (MSMEs) sector.